Anthropogenic influence in the Sado estuary (Portugal): a geochemical approach - Freitas, M.C.; Andrade, C.; Cruces, A.; Munhá, J.; Sousa, M. J.; Moreira, S.; Jouanneau, J. M.; Martins, L. (Journal of Iberian Geology, 2008)
Two areas of salt marsh in the Sado estuary – Faralhão, on the industrialized north margin and Malha da Costa, on the south bank, sheltered by a uninhabited sand spit – have been cored to study the geochemical signature of anthropogenic activity in recent (19th century onwards) intertidal sediments. Short cores were taken from each site from both the high and low marsh and were studied for texture, organic matter, pH, carbonates and geochemistry, including the heavy metals Cu, Pb and Zn. The marsh sediments are free of carbonate bioclasts and quite uniform in texture, consisting of acid to neutral clayey silt in addition to organic matter, which is higher in the top 20 cm. The vertical concentration profiles of heavy metals indicates enrichment in the top 30 cm of the sediment of the high marsh, in contrast with underlying high and low marsh sediment that has concentrations of metals at both studied sites similar to the Average Shale international reference/ continental crust sediments. The geochemical signal of anthropogenic influence in the marsh sediment was determined to have commenced from 1900-1920 using the sedimentation rates derived from 210Pb and 137Cs analyses. Spatial contrast in contamination levels was found within the estuary, with sediments of the Faralhão marsh showing higher enrichment factors of all metals. The anthropogenic increase of the supply of metal to the Sado estuary resulted from extensive exploitation of pyrite ore in the drainage basin until the1960’s; since that time, the sediments record a break in metal input, which resulted from a decline of the mining industry. However, in the marsh located closer to the industrial area (Faralhão) this break is followed by a local increase of heavy metal fluxes, which is interpreted as the result of intensification of anthropogenic influence. The comparison of metal concentrations in marsh sediments with target values established in quality guidelines indicates the studied area to be of environmental concern.